Shrinkage Volume, Compressive Strength, and Surface Roughness Y-TTRIA Stabilized Tetragonal Zirconia Polycrystal (Y-TZP) Using Binders Variation PVA:PEG as an Alternative Dental Implants Materials - Widaningsih, Widaningsih; Ariestania, Vivin; Ashrin, Meinar N.; Prananingrum, Widyasri; Rahmitasari, Fitri; Apituley, Terry; Joshua, Alvin; W., Yeremia Alfred; Fauzia, Bunga; Nanik, Chaterina D.; Lestari, Oka (European Journal of Dentistry, 2023)
Objective Yttria-stabilized tetragonal zirconia polycrystal (Y-TZP) is one of the materials that can be used as an alternative material for dental implants because of its good mechanical, biocompatible, and aesthetic properties. The binder used for ceramic processing to help bond is polyvinyl alcohol (PVA), which can increase the density of the ceramic material, and polyethylene glycol (PEG), which is used as a plasticizer for PVA, so it is pretty soft when pressed.Materials and Methods The sample was divided into five groups for volume shrinkage and compressive strength examination consisting of K1 (PVA 100%), K2 (PEG 100%), P1 (PVA:PEG 95:5), P2 (PVA:PEG 90:10), and P3 (PVA:PEG 85:15) and four groups on the surface roughness test, namely, K (PVA:PEG 1%), P1 (PVA:PEG 2%), P2 (PVA:PEG 3%), and P3 (PVA:PEG 4%). PVA:PEG binder with various concentrations was mixed with Y-TZP. The mixture was pressed using a uniaxial pressing method and continued by sintering at 1200°C for 4 hours.Statistical Analysis Least significant difference (LSD) test result showed that there was a significant difference in the compressive strength value and shrinkage volume between groups K1 and K2 and P3, and groups K2 with P1, P2, and P3. Post hoc LSD surface roughness test showed a significant difference between groups K with P2 and P3 and P1 and P3 (p < 0.05). There were no significant differences (p > 0.05) between K with P1 and P2 with P3.Results The Y-TZP group with the PVA binder mixture had the highest compressive strength, while the highest volume shrinkage was found in the PEG group. The next highest compressive strength and volume shrinkage values were found in the PVA:PEG group with a ratio of 95:5, 102.44 MPa, and 12.5%. The best PVA:PEG ratio of 95:5 is used to make surface roughness measurement samples. The best results showed that mixing Y-TZP with 4% PVA:PEG binder had the highest surface roughness compared to other PVA:PEG binders, namely 1.3450 μm.Conclusion From this study, it can be concluded that the best PVA:PEG percentage ratio to produce volume shrinkage and compressive strength is 95:5. The higher the concentration of PVA:PEG (95:5) binder mixed with Y-TZP, the higher the porosity will be.
Keywords: zirconia Y-TZP; PVA; PEG; shrinkage volume; compressive strength; surface roughness